Selective Targeting of a TNFR Decoy Receptor Pharmaceutical to the Primate Brain as a Receptor-Specific IgG Fusion Protein - Boado, Ruben J. (2010)
Decoy receptors, such as the human tumor necrosis factor receptor (TNFR), are potential new therapies for brain disorders. However, decoy receptors are large molecule drugs that are not transported across the blood-brain barrier (BBB). To enable BBB transport of a TNFR decoy receptor, the human TNFR-II extracellular domain was re-engineered as a fusion protein with a chimeric monoclonal antibody (MAb) against the human insulin receptor (HIR). The HIRMAb acts as a molecular Trojan horse to ferry the TNFR therapeutic decoy receptor across the BBB. The HIRMAb-TNFR fusion protein was expressed in stably transfected CHO cells, and was analyzed with electrophoresis, Western blotting, size exclusion chromatography, and binding assays for the HIR and TNFα. The HIRMAb-TNFR fusion protein was radiolabeled by trititation, in parallel with the radio-iodination of recombinant TNFR:Fc fusion protein, and the proteins were co-injected in the adult Rhesus monkey. The TNFR:Fc fusion protein did not cross the primate BBB in vivo, but the uptake of the HIRMAb-TNFR fusion protein was high and 3% of the injected dose was taken up by the primate brain. The TNFR was selectively targeted to brain, relative to peripheral organs, following fusion to the HIRMAb. This study demonstrates that decoy receptors may be re-engineered as IgG fusion proteins with a BBB molecular Trojan horse that selectively targets the brain, and enables penetration of the BBB in vivo. IgG-decoy receptor fusion proteins represent a new class of human neurotherapeutics.